Education and Training on MP-ASI Processing Skills for Posyandu Cadres in Randusari Village - Luluk Khusnul Dwihestie; Allania Hanung Putri Sekar Ningrum; Fitriana Mustikaningrum (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Stunting is a condition where a child's height does not match the standard at 2-5 years old. If proper stunting correction is not carried out, it will cause the development and growth of children to be inappropriate for their age. The most appropriate stunting correction is by providing balanced nutrition. Health cadres are elements of society that are expected to be pioneers in improving the healthy behavior of the community. Providing education and training to health cadres on age-appropriate complementary food processing is one step that is expected to improve the ability of cadres to provide a balanced complementary food menu for toddlers. From the results of this community service, it was found that there was an increase in the knowledge and skills of cadres in processing balanced nutritious local food ingredients for toddlers.